2014
DOI: 10.2147/copd.s68766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COPD in patients with lung cancer and advanced disease treated with chemotherapy and/or tyrosine kinase inhibitors

Abstract: While it is relatively well known that the prognosis of patients with lung cancer (LC) treated with surgery is worse in the presence of chronic obstructive pulmonary disease (COPD), it is unknown if this assessment can be extrapolated to patients with advanced disease treated with chemotherapy and/or tyrosine kinase inhibitors. The aim of our study is to analyze the clinical characteristics and survival rates in patients with LC and COPD, and to compare these to the patients without airflow obstruction. From 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 27 publications
(24 reference statements)
10
42
1
Order By: Relevance
“…This finding is consistent with previous studies, which also found COPD had no prognostic impact in patients with earlystage NSCLC or in patients with advanced NSCLC that received chemotherapy (10,19). In addition, the severity of emphysema in the present study was not well correlated with FEV 1 (%), which was also reported by Ueda et al (10).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies, which also found COPD had no prognostic impact in patients with earlystage NSCLC or in patients with advanced NSCLC that received chemotherapy (10,19). In addition, the severity of emphysema in the present study was not well correlated with FEV 1 (%), which was also reported by Ueda et al (10).…”
Section: Discussionsupporting
confidence: 93%
“…Zhai and colleagues found that coexisting COPD was associated with worse survival in patients with early-stage NSCLC undergoing surgical resection [110]. However, this association was insignificant in the study by Izquierdo and colleagues [112], who targeted patients with advanced lung cancer (stage IIIB/IV) treated with chemotherapy. In terms of COPD grade, there was a more apparent decrease in survival for patients with severe COPD, but not for those with mild-to-moderate COPD, as compared to non-COPD patients following lung cancer resection [78, 116].…”
Section: Prognosis Of Lung Cancer With Copdmentioning
confidence: 99%
“…Coexisting COPD is a poor prognostic factor for NSCLC, especially in men with squamous cell carcinoma even in never‐smokers . By contrast, other studies have reported that coexisting COPD does not affect the survival of NSCLC patients . However, there are limited data regarding the interaction between small cell lung cancer (SCLC) and COPD, mainly because the prevalence of SCLC is lower than that of other histological lung cancers, such as squamous cell carcinoma and adenocarcinoma .…”
Section: Introductionmentioning
confidence: 99%